EFFECTIVENESS OF USING A PENDULUM APPARATUS FOR DISTAL MOVEMENT OF THE FIRST PERMANENT MOLARS OF THE UPPER JAW IN CHILDREN WITHOUT ERUPTED SECOND PERMANENT MOLARS - Skrypnyk І.L.; Shnaider, S.A.; Pyndus, T.O.; Khoroz, L.M.; Jenca, A.; Jenchova, J.; Petrasova, A. (World of Medicine and Biology, 2024)
The study was devoted to evaluating the effectiveness of the Pendulum appliance for distal movement of the first permanent molars of the upper jaw in children whose second permanent molars had not yet erupted. Ten patients aged between 8 and 16 years with dentoalveolar anomalies participated in the research. Lateral cephalometric radiographs were used to assess angular and linear parameters before and after treatment with the Pendulum appliance. The appliance facilitated significant distalization of the first permanent molars, achieving an average movement of 7.48±0.64 mm over an average treatment duration of 3.26±0.37 months. Minor undesirable effects, such as mesial movement of anchorage teeth and slight incisor protrusion, were observed but resolved spontaneously within 2–3 weeks after appliance removal. These findings suggest that the Pendulum appliance is effective in distalizing first permanent molars in children without erupted second permanent molars, promoting optimal occlusal relationships and potentially simplifying future orthodontic treatment.